2023
DOI: 10.31234/osf.io/vs7p9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale disruptive activism strengthened environmental attitudes in the United Kingdom

Abstract: The 2019 London Extinction Rebellion was the first attempt by environmental protesters to create prolonged large-scale disruption in a Western capital city. The effects on public opinion were difficult to predict because protests seen as extreme can reduce support, but protests seen as justified can increase support. We studied longitudinal opinion changes in a nationally representative sample (n = 832) before, during, and after the rebellion, in conjunction with experimental analysis of the causal effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Indeed, there has been a wealth of work on climate activism in the United Kingdom and elsewhere, using measures other than press coverage to evaluate the outcome of a protest or action, such as public opinion polling and electoral results. For example, Kenward and Brick (2023) found that the 2019 Extinction Rebellion protests increased pro-environmental attitudes among members of the general public. Meanwhile significant polling by the UK-based Social Change Lab has found that disruptive actions can increase support for more moderate groups, that climate action can increase the likelihood of members of the public to engage in climate action, and that the Grand National protests led to simultaneous positive and negative outcomes (from Animal Rising's point of view; Ozden and Glover 2022, Ozden and Ostarek 2022, Ozden 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there has been a wealth of work on climate activism in the United Kingdom and elsewhere, using measures other than press coverage to evaluate the outcome of a protest or action, such as public opinion polling and electoral results. For example, Kenward and Brick (2023) found that the 2019 Extinction Rebellion protests increased pro-environmental attitudes among members of the general public. Meanwhile significant polling by the UK-based Social Change Lab has found that disruptive actions can increase support for more moderate groups, that climate action can increase the likelihood of members of the public to engage in climate action, and that the Grand National protests led to simultaneous positive and negative outcomes (from Animal Rising's point of view; Ozden and Glover 2022, Ozden and Ostarek 2022, Ozden 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale analysis of news media coverage of climate change in ten countries over a twelve year timespan found that protests have a significant impact on total media coverage, but that media mentions of protests comprise a relatively small proportion of total climate coverage (Hase et al 2021). There is strong experimental evidence that links news coverage of climate protests to public environmental attitudes, with positive coverage increasing pro-climate attitudes and negative coverage decreasing proclimate attitudes (Kenward and Brick 2023). The influence of media coverage on political elites has also been demonstrated experimentally (Wouters and Walgrave 2017) and through process tracing (Hutter and Vliegencourt 2018).…”
mentioning
confidence: 99%
“…A large-scale analysis of news media coverage of climate change in ten countries over a twelve year timespan found that protests have a significant impact on total media coverage, but that media mentions of protests comprise a relatively small proportion of total climate coverage (Hase, Mahl, Schäfer, Keller, 2021). There is strong experimental evidence that links news coverage of climate protests to public environmental attitudes, with positive coverage increasing pro-climate attitudes and negative coverage decreasing pro-climate attitudes (Kenward and Brick, 2023). The influence of media coverage on political elites has also been demonstrated experimentally (Wouters and Walgrave, 2017) and through process tracing (Hutter and Vliegencourt, 2016).…”
Section: Literature Review Of the Evidence Around Media And Activismmentioning
confidence: 99%
“…Indeed, there has been a wealth of work on climate activism in the United Kingdom and elsewhere, using measures other than press coverage to evaluate the outcome of a protest or action, such as public opinion polling and electoral results. For example, Kenward and Brick (2023) found that the 2019 Extinction Rebellion protests increased pro-environmental attitudes among members of the general public. Meanwhile significant polling by the UK-based Social Change Lab has found that disruptive actions can increase support for more moderate groups, that climate action can increase the likelihood of members of the public to engage in climate action, and that the Grand National protests led to simultaneous positive and negative outcomes (from Animal Rising's point of view; Ozden a, b, c).…”
Section: Limitationsmentioning
confidence: 99%
“…XR's strategy is based on collective action, using "non-violent civil disobedience" to protest about climate change. Past XR protests have increased environmental concern, and dissatisfaction with current government action (Kenward & Brick, 2023;Kountouris & Williams, 2023).…”
Section: Introductionmentioning
confidence: 99%